Effects of a newly developed potent orexin-2 receptor-selective antagonist, compound 1 m, on sleep/wakefulness states in mice - Etori, Keishi; Saito, Yuki; Tsujino, Natsuko; Sakurai, Takeshi (Frontiers in Neuroscience, 2014)
Orexins (also known as hypocretins), which are hypothalamic neuropeptides, play critical roles in the regulation of sleep/wakefulness states by activating two G-protein coupled receptors (GPCRs), orexin 1 (OX1R) and orexin 2 receptors (OX2R). In order to know the difference between effects of OX2R-selective antagonists (2-SORA) and dual orexin receptor antagonists (DORA), and to understand the mechanisms underlying orexin-mediated regulation of sleep/wakefulness states, we examined the effects of a newly developed 2-SORA, Compound 1m (C1m), and a DORA, suvorexant, on sleep/wakefulness states in C57BL/6J mice. After oral administration in the dark period, both C1m and suvorexant exhibited potent sleep-promoting properties with similar efficacy in a dose-dependent manner. While C1m did not increase NREM and REM sleep episode durations, suvorexant induced longer episode durations of NREM and REM sleep as compared with both the vehicle- and C1m-administered groups. When compounds were injected during light period, C1m did not show a significant change in sleep/wakefulness states in the light period, whereas suvorexant slightly but significantly increased the sleep time. We also found that C1m did not affect the time of REM sleep, while suvorexant markedly increased it. This suggests that although OX1R-mediated pathway plays a pivotal role in promoting wakefulness, OX1R-mediated pathway also plays an additional role. OX1R-mediated pathway also plays a role in suppression of REM sleep. Fos-immunostaining showed that both compounds affected the activity of arousal-related neurons with different patterns. These results suggest partly overlapping and partly distinct roles of orexin receptors in the regulation of sleep/wakefulness states.